Vein identification using line features - Li, Fang (2013)
This paper proposes a novel technique to analyze the infrared vein patterns in the back of the hand for biometric purposes. The line-patterns are retrieved in a rotation and translation invariant manner to tackle broken line problem. A set of pair-wise angle relationships among lines are extracted to present the local structure of line pattern. In order to keep positional information as well, dynamic region division technique is proposed. Pair-wise angle relationships are simple, invariant to translation and rotation, robust to end-point erosion and segment error, and sufficient for discrimination. The matching experiment has shown encouraging results which implicate that line segments can provide sufficient information for vein recognition.